Brand Advertising in an Access–Ownership World: How Marketing Channels Impact Message Persuasiveness. Issue 1 (3rd April 2017) - Harding, Lora Mitchell; Schenkel, Mark T.
Abstract : Recent research has sought to identify drivers of preference for access-based consumption over ownership. Although much of this research highlights ideological reasons consumers may prefer access options, other empirical work suggests that functional reasons may be stronger drivers. We examine whether functional appeals will always result in more favorable attitudes toward access offerings or if and when ideological appeals will be equally or more persuasive. Building on the satisficing, maximizing, and brand personality literatures, we propose that people are more likely to satisfice in an access marketing channel, becoming more persuaded by appeals that fit with—or meet—minimum expectations given the brand's personality. In contrast, people are more likely to maximize in an ownership marketing channel, becoming more persuaded by appeals that do not fit with—or exceed—minimum expectations given the brand's personality. The results of two experiments with competent, exciting, and sincere brands largely support these hypotheses.